New wave approach to the conformable resonant nonlinear Schodinger's equation with Kerr-law nonlinearity - Yel, Gulnur; Bulut, Hasan (Springer, 2022)
In this research, we analyze travelling wave solutions of the conformable resonant nonlinear Schrodinger's equation with Kerr-law nonlinearity by using an analytical approach which is the rational sine-Gordon expansion method. The purposed technique is a significant method to solve nonlinear evolution equations having high nonlinearity. We found some explicit solutions, including bright soliton and dark soliton, which have important roles in fields such as quantum physics, optical fibres by this way. We illustrate some graphics corresponding to the obtained wave solutions under the appropriate coefficients to help better understand their physical meaning of them.
Keywords: Resonant nonlinear Schrodinger's equation; The rational sine-Gordon expansion method; Conformable derivative